Structure, use, and syntactic ecology in language obsolescence. (21st June 2017) - Adger, David
Abstract: Nancy Dorian's foundational work on the loss of Gaelic in the East Sutherland communities continues to provide important insights into the nature of the process of language change in situations of obsolescence. In this article I look at a subset of Dorian's data from the perspective of current syntactic theory, and argue that the connected loss of such apparently different constructions as objects of non-finite verbs, inalienable possessive structures, and a range of passives, and the concomitant restructuring of the grammar, all follow from the interaction between a reduction in agreement features on a functional head and the broad syntactic ecology of the language. This approach makes sense of why these apparently disparate constructions all undergo the particular kinds of change that are seen, changes which are mysterious from the perspective that an obsolescing language should alter to become more like the dominant language (in this case English) which is replacing it. Résumé: Le travail fondamental de Nancy Dorian sur la perte du gaélique dans les communautés de East Sutherland continue de fournir des informations importantes sur la nature du processus de changement linguistique dans les situations d'obsolescence. Dans cet article, j'examine un sous-ensemble des données de Dorian à la lumière de la théorie syntaxique actuelle et soutiens que la perte connexe de constructions pourtant différentes, comme les objets de verbes non tensés, les structures possessives inaliénables et une gamme de constructions passives, et la restructuration concomitante de la grammaire, découlent de l'interaction entre une réduction des caractéristiques d'accord sur une tête fonctionnelle et l'écologie syntaxique de la langue de manière plus générale. Cette approche permet de comprendre pourquoi ces constructions en apparence hétérogènes subissent toutes les changements particuliers qui ont été observés, et qui paraissent mystérieux si l'on croit qu'une langue en voie d'obsolescence devrait changer de manière à ressembler davantage à la langue dominante (ici l'anglais), qui est en train de la remplacer.